Effect of diabetes mellitus on risk of latent TB infection in a high TB incidence area: a community-based study in Taiwan. Issue 10 (28th October 2019) - Lin, Ching-Hsiung; Kuo, Shu-Chen; Hsieh, Ming-Chia; Ho, Shang-Yun; Su, Ih-Jen; Lin, Sheng-Hao; Chi, Chia-Yu; Su, Shih-Li; Liao, Chiung-Ying; Chen, Yee-Chun; Hsu, Shang-Ren; Huang, Yuan-Chun; et al.
Abstract : Objective: To investigate the association between diabetes and latent tuberculosis infections (LTBI) in high TB incidence areas. Design: Community-based comparison study. Setting: Outpatient diabetes clinics at 4 hospitals and 13 health centres in urban and rural townships. A community-based screening programme was used to recruit non-diabetic participants. Participants: A total of 2948 patients with diabetes aged older than 40 years were recruited, and 453 non-diabetic participants from the community were enrolled. Primary and secondary outcome measures: The interferon-gamma release assay (IGRA) and the tuberculin skin test were used to detect LTBI. The IGRA result was used as a surrogate of LTBI in logistic regression analysis. Results: Diabetes was significantly associated with LTBI (adjusted OR (aOR)=1.59; 95% CI 1.11 to 2.28) and age correlated positively with LTBI. Many subjects with diabetes also had additional risk factors (current smokers (aOR=1.28; 95% CI 0.95 to 1.71), comorbid chronic kidney disease (aOR=1.26; 95% CI 1.03 to 1.55) and history of TB (aOR=2.08; 95% CI 1.19 to 3.63)). The presence of BCG scar was protective (aOR=0.66; 95% CI 0.51 to 0.85). Duration of diabetes and poor glycaemic control were unrelated to the risk of LTBI. Conclusion: There was a moderately increased risk of LTBI in patients with diabetes from this high TB incidence area. This finding suggests LTBI screening for the diabetics be combined with other risk factors and comorbidities of TB to better identify high-risk groups and improve the efficacy of targeted screening for LTBI.